The Effect Of Trade Specialization And Institutional Quality On Intra-Asean Trade - A Bakar, Norhayati (2017)
Intra-ASEAN trade is stagnant at 20% to 25% for the past few decades. This is partly because ASEAN members are overl-reliant on non-ASEAN countries for their exports. Several suggestions have been put forward such as exchange rates and trade agreement which observed so far as having limited effect to increase intra-ASEAN trade. In this study, we propose and examine the role of trade specialization and the quality of institutions among ASEAN for a period between 1996 and 2015. ASEAN countries are generally endowed with similar resources have a tendency to compete with each other for similar products.